Premature ovarian insufficiency restoration after chemotherapy: current achievements and future prospects on its treatment or management - Hamideh Aboutalebi; Shayan Vafaei; Mohammad Aboutalebi; Hengameh Dortaj; Fatemeh Alipour; Alireza Ebrahimzadeh- Bideskan (Journal of Ovarian Research)
Abstract One of the important discussions in assisted reproductive technology (ART) is to maintain fertility in those who are at risk of losing their fertility for various reasons, including cancer and the use of anti-cancer therapies, hence finding a way to maintain fertility during chemotherapy, is vital. Nowadays, in addition to successfully treating patients, oncologists have also focused their attention on preserving their patients' potential of the latter to conceive. Chemotherapy-related ovarian failure, which manifests as a non-physiological form of amenorrhea, can cause dysfunction of the ovary. It is hypothesized that chemotherapeutic agents may cause DNA damage, accelerate follicular apoptosis, oxidative stress, resulting in loss of ovarian reserve function. Hence investigation on utilization of alternatives in order to maintain ovarian function and fertility in cancer survivors seems important. This review provides an update on available and potential future prospects for fertility preservation in women treated with chemotherapy.